Sebaran Keberadaan Kukang Jawa (Nycticebus javanicus) di Kawasan Taman Buru Masigit Kareumbi - Zidni Robbi Rodliyya (Wanamukti: Jurnal Penelitian Kehutanan, 2021)
According to previous observations, the distribution of habitat and population of slow lorises in Indonesia shows that slow lorises are found mostly in plantation habitats, agricultural land, and  community forests where the available feed supply is in the form of fruits, insects and small reptiles. Taman Buru Masigit Kareumbi is one of the areas that has a level of vulnerability to the illegal hunting of slow lorises outside the forest area that enters the community land area. One of the habitats for the Javan slow loris is the Masigit Kareumbi Hunting Park (TBMK). Observations in the study used the line transect method (line transect) combined with the spot lighting method and GPS mapping, with a sampling intensity of 1% in accordance with P.67 /Menhut-II / 2016 regarding criteria and forest inventory standards for sampling intensity. The survey was carried out by walking slowly at an average speed of 1 km / hour and systematically looking for and observing the presence of slow lorises on the forest floor, lower canopy, middle canopy and upper canopy. The existence of slow lorises in Taman Buru Masigit kareumbi is spread across utilization blocks in 3 locations,  namely Bagus,  Hadun, and Cimulu, and 5 Javan slow lorises were found directly in the field during the research.